Proceedings of the Annual International Conference of Business and Public Administration (AICoBPA 2018) 2019
DOI: 10.2991/aicobpa-18.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Immersion and Telepresence in Gamified Virtual Tourism Experience toward Tourist’s Behaviour

Abstract: Research and application of virtual tourism has been rapidly developing in the industrial era 4.0. However, research about perspective of tourist behavior in virtual tourism is still lacking, especially in Indonesia. This research method used is explanatory research with a survey that implemented on tourist to gamification-based virtual tourism presented of Virtual Arena in Jawa Timur Park 3. The results of the analysis shows that the ability to create virtual experiences in the form of immersion is not necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Also, authors confirmed the effectiveness of 360• VR technology usage to promote historical attractions and enrich the user's experience (Argyriou et al, 2020;Škola et al, 2020). So the expression of VR technologies has become a crucial update in the latest few years and will continue in the future, as it generates economic opportunities through the support of technological innovation (Bafadhal and Hendrawan, 2019) and serves to improve the pre-, during, and post-trip experiences of visitors. Additionally, these technologies are creating a new tourism paradigm (Zhang et al, 2022;de Lurdes Calisto and Sarkar, 2024), named virtual tourism (VT), which is predicated on an immersive online environment modeled after actual tourist destinations (Bogicevic et al, 2019).…”
Section: Introductionmentioning
confidence: 77%
“…Also, authors confirmed the effectiveness of 360• VR technology usage to promote historical attractions and enrich the user's experience (Argyriou et al, 2020;Škola et al, 2020). So the expression of VR technologies has become a crucial update in the latest few years and will continue in the future, as it generates economic opportunities through the support of technological innovation (Bafadhal and Hendrawan, 2019) and serves to improve the pre-, during, and post-trip experiences of visitors. Additionally, these technologies are creating a new tourism paradigm (Zhang et al, 2022;de Lurdes Calisto and Sarkar, 2024), named virtual tourism (VT), which is predicated on an immersive online environment modeled after actual tourist destinations (Bogicevic et al, 2019).…”
Section: Introductionmentioning
confidence: 77%
“…The more varied the needs of many schools to carry out outdoor learning activities in the form of edutourism, the more business opportunities are opened that require a lot of new workers (Ram Choudhary & Srivastava, 2022). An edutourism location requires a lot creative human resources to build an educational tourism location that is increasingly more attractive and meets consumer needs (Bafadhal & Hendrawan, 2019). This will really attract consumers to pay for all the facilities provided and really support all learning activities in outdoors by the school.…”
Section: Resultsmentioning
confidence: 99%
“…Virtual tours can be considered a possible action "that can improve the tourist attractiveness of a city, especially in the case of interesting unknown or inaccessible aspects" [10] as well as a common practice to address inaccessibility. Virtual tourism can be interpreted as "a digital presentation of the actual tourist attraction, where geometric properties of three-dimensional space are communicated to virtual tourists (also called tele-tourists) in such a way that they can provide immersion and telepresence from tourist objects that seem to be real" [30].…”
Section: Engaging With a Destination Through 360-degree Panoramic Vir...mentioning
confidence: 99%